Transformation of the Institution of Anti-Trust Regulation (Mechanism and Concept) - K. A. Kudryavtsev (Вестник Российского экономического университета имени Г. В. Плеханова)
To find a new vector of developing anti-trust regulation the article researches mechanism of its transformation. In the process of research the academic hypothesis is proved, i. e. anti-trust regulation transforms in line with the change of models of state economy regulation and subject to the economic cycle is used by state as a tool of influencing the results of goods markets functioning with limited and developed competition. The disclosed cause- and effect links determining the transformation mechanism made it possible to identify stages of developing antitrust regulation in the world and in Russia. In order to overcome backwardness of economy and implement the National plan of developing competition  in the Russian Federation  conceptual principles were developed for the new phase of anti-trust regulation, which are shown in the model of interest balance with the respective key indicators. The presented model is the development of the Harvard paradigm ‘structure – behavior – result’ that was later supplemented with basic conditions and state policy, whose system includes anti-trust regulation. Therefore, with regard to designed conceptual principles with state regulation of goods market what is the most important is the balance of interests of entities of market – state, business entities and customers that form the structure, behavior and result.